Community Mobilization for Slum Upgrading through Sanitation in Roma Informal Settlements in the Paris Region - Chaudhuri, Ipsita Nita (Frontiers in Public Health, 2017)
Background Community-based processes addressing environment, housing, and health issues may decrease health inequities by addressing social, economic, and political health determinants more effectively. Yet little analysis of their effectiveness has been undertaken and their potential transfer to marginalized groups in rich country settings. In Europe, stark health inequalities are seen among the Roma, Europe’s most impoverished community who often reside in informal settlements suffering from illiteracy, inadequate housing, and lack of water and sanitation. This paper assesses a dry sanitation project in a Roma informal settlement in the Paris region to improve their living conditions. Methods Between 2014 and 2017, multiple stakeholders were involved in a participatory process of design, construction, and maintenance of toilets. Interviews, mapping, model construction, and facilitated discussion were used to identify design features and follow-up indicators. Field notes, videos, questionnaires, and observation provided data for monitoring and evaluation. For questionnaires delivered to women in the community, a cross section time series was conducted to due to migration. Results Despite issues related to maintenance, the overall quality of life of women improved after toilet construction. This included indicators for comfort, cleanliness, practicality, privacy, security, and menstrual hygiene management. Furthermore, fewer women restrained themselves from relieving themselves or from drinking less water to avoid urinating. Odors continued to be an issue. Self-reporting of illnesses, such as diarrhea and urinary tract infections, were not reliable due to the vague description of these illnesses and the potential recall bias. Appropriate sanitation in informal settlements is a necessity as shown by feedback from Roma women and the literature. However, a more sustainable toilet project would have required an adequate budget, good quality materials, accountability, and buy in from all inhabitants as well as good relationships between the chief and all stakeholders in the settlement. Furthermore, provision should have been made for vulnerable and less autonomous inhabitants to ensure proper follow-up and maintenance. Conclusion/recommendations Safe water and sanitation is essential to decrease health inequities. Formative research, identifying natural leaders, sanitation committee formation, outcome indicator and baseline questionnaire development, appropriate messages and toilet design and placement, long-term follow-up, and political support are elements for effective interventions with the Roma. Potential attrition and reporting bias should be considered in monitoring and evaluation.